Australia's Lost Capitol. Issue 2 (2nd July 2016) - Vernon, Christopher
Abstract : In 1911, the Commonwealth of Australia—then only a decade old—self-confidently launched an international design competition for its federal capital, afterward named Canberra. Chicagoans Walter Burley Griffin and Marion Mahony Griffin famously won the contest the next year (no doubt to the consternation of their former employer, Frank Lloyd Wright). In 1914, the couple arrived in Australia to begin implementing their prizewinning plan. Based upon extensive archival research, this study surveys the couple's unrealized Capitol building, envisaged as Canberra's—and the nation's—cultural epicenter. It also reconstructs the disappointing saga as to why the edifice was never constructed.